Plastid-Targeted Cyanobacterial Flavodiiron Proteins Maintain Carbohydrate Turnover and Enhance Drought Stress Tolerance in Barley - Shahinnia, Fahimeh; Tula, Suresh; Hensel, Goetz; Reiahisamani, Narges; Nasr, Nasrin; Kumlehn, Jochen; Gómez, Rodrigo; Lodeyro, Anabella F.; Carrillo, Néstor; Hajirezaei, Mohammad R. (Frontiers in Plant Science, 2021)
Chloroplasts, the sites of photosynthesis in higher plants, have evolved several means to tolerate short episodes of drought stress through biosynthesis of diverse metabolites essential for plant function, but these become ineffective when the duration of the stress is prolonged. Cyanobacteria are the closest bacterial homologs of plastids with two photosystems to perform photosynthesis and to evolve oxygen as a byproduct. The presence of Flv genes encoding flavodiiron proteins has been shown to enhance stress tolerance in cyanobacteria. In an attempt to support the growth of plants exposed to drought, the Synechocystis genes Flv1 and Flv3 were expressed in barley with their products being targeted to the chloroplasts. The heterologous expression of both Flv1 and Flv3 accelerated days to heading, increased biomass, promoted the number of spikes and grains per plant, and improved the total grain weight per plant of transgenic lines exposed to drought. Improved growth correlated with enhanced availability of soluble sugars, a higher turnover of amino acids and the accumulation of lower levels of proline in the leaf. Flv1 and Flv3 maintained the energy status of the leaves in the stressed plants by converting sucrose to glucose and fructose, immediate precursors for energy production to support plant growth under drought. The results suggest that sugars and amino acids play a fundamental role in the maintenance of the energy status and metabolic activity to ensure growth and survival under stress conditions, that is, water limitation in this particular case. Engineering chloroplasts by introducing Flv genes, therefore, has the potential to improve plant productivity wherever drought stress represents a significant production constraint.